2023
DOI: 10.1007/s11270-023-06230-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Removal of Phosphate from Water by Adsorption Using Biopolymer Chitosan Beads

Abstract: The need for clean water is the most basic human right. Water scarcity will be one important environmental problem of all countries in the future. Phosphate is a harmful matter for public health and the environment. In this study, the removal of phosphate from water by chitosan, which is an environmentally friendly material, was investigated. Chitosan adsorbent spheres were prepared for phosphate separation from water by adsorption, which is a feasible method. The effects of phosphate concentration, adsorbent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In the crystallization process calcium reacts with hydroxide ions that exist in the aqueous alkaline solution to remove phosphate ions in the form of hydroxyapatite 10 , 14 . Due to the hydrophilic and three-dimensional polymeric network of polymer hydrogel, it is observed that polymer hydrogel is effective to be used as an adsorbent for phosphate ion removal from wastewater 9 , 14 16 . Because, nanomaterials/nanoparticles, snail shell dust and, carbon-based materials (activated carbon and biochar) have exceptionally high surface areas and phosphate adsorption properties, they are widely used for phosphate removal from wastewater 11 , 17 23 .…”
Section: Introductionmentioning
confidence: 99%
“…In the crystallization process calcium reacts with hydroxide ions that exist in the aqueous alkaline solution to remove phosphate ions in the form of hydroxyapatite 10 , 14 . Due to the hydrophilic and three-dimensional polymeric network of polymer hydrogel, it is observed that polymer hydrogel is effective to be used as an adsorbent for phosphate ion removal from wastewater 9 , 14 16 . Because, nanomaterials/nanoparticles, snail shell dust and, carbon-based materials (activated carbon and biochar) have exceptionally high surface areas and phosphate adsorption properties, they are widely used for phosphate removal from wastewater 11 , 17 23 .…”
Section: Introductionmentioning
confidence: 99%